2023
DOI: 10.3390/en16155847
|View full text |Cite
|
Sign up to set email alerts
|

A ZnO Gas Sensor with an Abnormal Response to Hydrogen

Abstract: ZnO is a commonly used material for hydrogen gas sensors. In this study, a ZnO nanofiber film with a diameter of approximately 60 nm was synthesized by the electrospinning method. Compared to previously reported ZnO hydrogen gas sensors, an abnormal phenomenon was observed here, where the resistance of the ZnO nanofiber film increased upon exposure to hydrogen gas in the temperature range from 210 °C to 330 °C. The physical mechanism of this phenomenon was explored through microstructure analysis and DFT simul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…Within the temperature range of 210–330 °C, upon exposure to 20 ppm H 2 gas, the resistance of the ZnO nanofiber film increased, and the sensitivity ∼28.84% at 270 °C. 28 Kumar et al reported room temperature chemiresistive sensors using hexadecafluorinated copper phthalocyanine (F16CuPc) and graphene oxide (rGO) hybrid materials. The fabricated sensor is highly sensitive to Cl 2 gas with a detection limit up to ppb level.…”
Section: Introductionmentioning
confidence: 99%
“…Within the temperature range of 210–330 °C, upon exposure to 20 ppm H 2 gas, the resistance of the ZnO nanofiber film increased, and the sensitivity ∼28.84% at 270 °C. 28 Kumar et al reported room temperature chemiresistive sensors using hexadecafluorinated copper phthalocyanine (F16CuPc) and graphene oxide (rGO) hybrid materials. The fabricated sensor is highly sensitive to Cl 2 gas with a detection limit up to ppb level.…”
Section: Introductionmentioning
confidence: 99%